The not-so-helpless princess - Hoena, B. A; Cunyat, Pol (North Mankato, Minnesota Stone Arch Books, a Capstone imprint, 2017)
The King summons Thud and Blunder, a pair of nine-year-old knights, and sends them to Castle Kidnapt to "rescue" the five-year-old princess from the castle overrun by ogres--however it seems that it is the ogres who need rescuing
Comic strips
RL: 2.4
1 2 13 15
Keywords: Ghouls and ogres -- Juvenile fiction; Knights and knighthood -- Juvenile fiction; Princesses -- Juvenile fiction; Humorous stories; Knights and knighthood -- Fiction; Monsters -- Fiction; Princesses -- Fiction; Humorous fiction